2015
DOI: 10.1007/s12263-015-0482-2
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-regulated gene expression differs in celiac disease patients according to the age of presentation

Abstract: Celiac disease is an intestinal disease which shows different symptoms and clinical manifestations among pediatric and adult patients. These variations could be imputable to age-related changes in gut architecture and intestinal immune system, which could be characterized by gene expression differences possibly regulated by miRNAs. We analyzed a panel of miRNAs and their target genes in duodenal biopsies of Marsh 3AB and 3C pediatric celiac patients, compared to controls. Moreover, to assess variation of expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 53 publications
1
40
0
Order By: Relevance
“…In addition, circulating miR-31-5p in untreated CD patients displayed a significantly decline compared to controls. Moreover, there is no statistically significant difference in miRNA levels between controls and CD patients on a gluten-free diet (2). In a study performed by Magni et al (2014) in the duodenum of adult CD patients, the significantly decreased expression of miR-192-5p, miR-31-5p, miR-338-3p, and miR-197 were demonstrated as compared with controls (5).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In addition, circulating miR-31-5p in untreated CD patients displayed a significantly decline compared to controls. Moreover, there is no statistically significant difference in miRNA levels between controls and CD patients on a gluten-free diet (2). In a study performed by Magni et al (2014) in the duodenum of adult CD patients, the significantly decreased expression of miR-192-5p, miR-31-5p, miR-338-3p, and miR-197 were demonstrated as compared with controls (5).…”
Section: Discussionmentioning
confidence: 93%
“…After that, they evaluated the circulating miRNA patterns in untreated CD patients or on a gluten-free diet compared to controls. They found that miR-31-5p and miR-338-3p were underexpressed in the duodenum samples of CD patients (2). In addition, circulating miR-31-5p in untreated CD patients displayed a significantly decline compared to controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13,14 Multiple mechanisms have been implicated in tTreg development and suppressive function, including more recently miRNA's effects on posttranscriptional gene regulation. [15][16][17][18] The miR-146 family includes 2 main members, miR-146a and miR-146b, which are both highly expressed and play important roles in cell proliferation and function in diverse cell types, including T and B cells. Studies of breast cancer cells have shown a Foxp3-dependant increase in the expression of miR-146b and, to a lesser extent, miR-146a, 19 which results in reduced breast cancer cell proliferation and enhanced apoptosis via negative regulation of nuclear factor kB (NF-kB).…”
Section: Cd25mentioning
confidence: 99%